PENGARUH HARGA, PROMOSI DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN ONLINE SHOPEE DI BANDAR LAMPUNG - Audia Indah Banowati; Aripin Ahmad; Nuzul Inas Nabila (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The development of technology towards an all-digital direction in Indonesia is currently growing rapidly, causing changes in consumer behavior that shifts from offline shopping to online shopping. One of the most popular E-Commerce-based online shopping sites in Indonesia is Shopee. In this condition, purchasing decisions are influenced by price, promotion and trust. The purpose of this study was to determine whether there was an effect of price, promotion, and trust on Shopee's online purchasing decisions in Bandar Lampung. The sampling used in this research is using non-probability sampling method with purposive sampling technique. The number of samples used in this study were 100 respondents. Analysis of the data used is multiple linear regression analysis. The results of this study indicate that: (1) Price has a significant effect on Shopee online purchasing decisions in Bandar Lampung (2) Promotion has a significant effect on Shopee online purchasing decisions in Bandar Lampung (3) Trust has a significant effect on Shopee online purchasing decisions in Bandar Lampung and ( 4) Price, Promotion and Trust have a significant effect on Shopee's online purchasing decisions in Bandar Lampung.